Evaluation of forestry research capacity in eastern and southern Africa - Kowero, G.S.; Spilsbury, M.J. (1997)
A methodology for evaluating research capacity is outlined and applied to 19 institutions in 10 countries. The indicators used are not comprehensive but are useful for evaluating the performance of existing research capacity. The results reemphasised the need to give priority to manpower recruitment, training and development since only about half of all scientists in the institutions surveyed have sufficient training and research exposure. Research management also requires urgent attention. About 17% of the institutions surveyed allocate more than 20% of their research budgets to the transfer and dissemination of research findings to 'user groups' and about 28% of staff time is said to be allocated to this purpose. This raises questions about how research priorities and programmes are formulated and about the relevance of the research conducted. There is considerable interaction between institutions in the region but how this can be translated into coordinated collaborative activities remains unclear.